2015
DOI: 10.1038/ncomms6877
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur-impregnated flow cathode to enable high-energy-density lithium flow batteries

Abstract: Redox flow batteries are promising technologies for large-scale electricity storage, but have been suffering from low energy density and low volumetric capacity. Here we report a flow cathode that exploits highly concentrated sulphur-impregnated carbon composite, to achieve a catholyte volumetric capacity 294 Ah l À 1 with long cycle life (4100 cycles), high columbic efficiency (490%, 100 cycles) and high energy efficiency (480%, 100 cycles). The demonstrated catholyte volumetric capacity is five times higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(79 citation statements)
references
References 49 publications
(125 reference statements)
4
73
0
Order By: Relevance
“…Chen et al. reported a non‐aqueous sulfur‐impregnated carbon composite dispersion as the catholyte and combined it with a Li (s) anode 111. This setup leads to an average discharging voltage of 2 V and an immense volumetric capacity of 294 Ah L −1 .…”
Section: History: “The Metal Age”mentioning
confidence: 99%
“…Chen et al. reported a non‐aqueous sulfur‐impregnated carbon composite dispersion as the catholyte and combined it with a Li (s) anode 111. This setup leads to an average discharging voltage of 2 V and an immense volumetric capacity of 294 Ah L −1 .…”
Section: History: “The Metal Age”mentioning
confidence: 99%
“…[ 29 ] We found that the LiI not only increases the reversible volumetric capacity of the catholyte but also improves the electrochemical utilization of insulating sulfur. We evaluated a number of com- Adding LiI increases the reversible volumetric capacity of the catholyte.…”
Section: Electrochemical Performance Of the Lii-s/c Mrssl Catholytementioning
confidence: 98%
“…In conventional all-liquid RFBs [ 34,35 ] and semi-solid RFBs, [26][27][28][29] the liquid phase includes solvents, dissolved salts, and/or soluble active species. In the MRSSL approach, we employ bi-functional soluble active species that not only contribute reversible capacity but also support ion conduction as an electrolyte salt, to maximize the capacity contribution from the liquid phase.…”
Section: Design Concept Of the Mrssl Flow Batterymentioning
confidence: 99%
See 1 more Smart Citation
“…[225][226][227][228] For the traditional Li-S batteries, the formation of soluble polysulde species leads to detrimental self-discharge. However, such attributes can be utilized in ow battery systems.…”
mentioning
confidence: 99%